Negotiated compliance at the street level: Personalizing immunization in England, Israel and Sweden. (27th December 2018) - Gofen, Anat; Blomqvist, Paula; Needham, Catherine E.; Warren, Kate; Winblad, Ulrika
Abstract : Often portrayed as behaviour that is inconsistent with policy goals, public noncompliance poses a significant challenge for government. To explore what compliance efforts entail on the ground, this study focuses on childhood immunization as a paradigmatic case where a failure to ensure compliance poses a public health risk. The analysis draws on 48 semi‐structured interviews with frontline nurses and regional/national public health officials in England ( N = 15), Sweden ( N = 17) and Israel ( N = 16), all of which have experienced periodic noncompliance spikes, but differ in direct delivery of vaccination provision. Compliance efforts emerged as a joint decision‐making process in which improvisatory practices of personalized appeals are deployed to accommodate parents' concerns, termed here 'street‐level negotiation'. Whereas compliance is suggestive of compelling citizens' adherence to standardized rules, compliance negotiation draws attention to the limited resources street‐level workers have when encountering noncompliance and to policy‐clients' influence on delivery arrangements when holding discretionary power over whether or not to comply.